Localization of DNA sequences required for human centromere function through an analysis of rearranged Y chromosomes. - Tyler-Smith, C; Oakey, R; Larin, Z; Fisher, R; Crocker, M; Affara, N; Ferguson-Smith, M; Muenke, M; Zuffardi, O; Jobling, M (1993)
We have localized the DNA sequences required for mitotic centromere function on the human Y chromosome. Analysis of 33 rearranged Y chromosomes allowed the centromere to be placed in interval 8 of a 24-interval deletion map. Although this interval is polymorphic in size, it can be as small as approximately 500kb. It contains alphoid satellite DNA and approximately 300kb of adjacent Yp sequences. Chromosomes with rearrangements in this region were analysed in detail. Two translocation chromosomes and one monocentric isochromosome had breakpoints within the alphoid array. Of 12 suppressed Y centromeres on translocation chromosomes and dicentric isochromosomes that were also analysed two showed deletions one of which only removed alphoid DNA. These results indicate that alphoid DNA is a functional part of the Y chromosome centromere.